The Effectiveness of a Renewable Energy E-Worksheet in STEM-Project-Based Learning to Improve Students' Critical Thinking and Collaboration Skills - Rachmawati, Fridiani Asiyah; Wiyatmo, Yusman (Universitas Muhammadiyah Makassar, 2025)
The integration of 21st-century competencies, particularly critical thinking and collaboration, has become essential in physics education. However, the abstract concept of renewable energy poses learning challenges for high school students, despite its fundamental importance in physics education and relevance to sustainability. This study investigates the effectiveness of a STEM-project-based electronic worksheet (e-worksheet) designed to enhance students’ critical thinking and collaboration abilities. A quasi-experimental design with a randomized cluster sampling technique was used, involving 50 Grade X students from SMA Negeri 1 Subang. The experimental group received instruction through a renewable energy e-worksheet aligned with STEM and Project-Based Learning (PjBL) models, while the control group experienced conventional teaching. Data were collected through pre-and post-tests and questionnaires and analyzed using N-Gain and Cohen’s d-effect size. The results show high N-Gain scores in the experimental group for critical thinking (0.72) and collaboration skills (0.75), in contrast to moderate scores in the control group. This suggests a significant learning gain attributable to the integrated e-worksheet. The study's novelty lies in the integration of a renewable energy project, digital interactivity via Liveworksheets, and structured STEM-PjBL syntax, providing a holistic, engaging learning experience. The research concludes that STEM-PjBL e-worksheets are effective in promoting 21st-century competencies and can address instructional gaps in current physics education. This approach contributes to developing sustainable thinking and teamwork abilities, preparing students for future interdisciplinary challenges in science and technology